Profile of Pre-Service Math Teachers’ Conception about the Definition of Limit Functions Based on Mathematical Ability - Usman, Usman; Hasbi, Muhammad; Muslem, Asnawi (Jurnal Pendidikan Progresif, 2024)
Profile of Pre-Service Math Teachers' Conception about the Definition of Limit Functions Based on Mathematical Ability. Objective: The study aims to explore the profile of pre-service math teachers' Conception about the definition of limit functions based on mathematical ability between high and low ability and to find out their perceptions on the topic. Methods: The methods used in this study were mixed-methods in nature; quantitative and qualitative. The participants of the study are 64 pre-service math teachers who are studying in the fifth-semester academic year 2022, Faculty of Teacher Training and Education, Syiah Kuala University. The reason of selecting this participant is because they have gained experience studying calculus and objective analysis. The data collection for this study is obtained through math ability tests on limit conception tests and interviews. The data are analysed by using descriptive quantitative and qualitative.  The data from the interview are analysed by reducing data, exposing, interpreting, and concluding. Findings: This study reported that high pre-service math teachers group outperformed the low-ability group in terms of math tests. In addition, The pre-service math teachers’ perceptions on expressing ideas, and explaining formal definitions of the limit function and mental image were relatively good. Conclusion: The study concluded that the profile of high ability of the pre-service math teachers performed better than those low in math test competence and their understanding of the definition of limit function, mental image and the concepts of limit function and limit function relation were relatively good. Of course, this study has a limitation in terms of comprehensive information related to understanding math concepts and practice. Keywords: profile, pre-service teacher, conception, limit function, mathematical ability.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202451